Nanocomposites for Multifunctional Sensors: A Comprehensive Bibliometric Exploration - Antonio del Bosque; Georgios Lampropoulos; Diego Vergara (Nanomaterials)
Multifunctional nanocomposites have become critical components in advancing sensing technologies, owing to their exceptional integration of mechanical, electrical, thermal, and optical properties. The research landscape of nanocomposites for sensing applications from 2002 to 2024 is examined in this bibliometric review. It identifies key trends, influential works, prominent research areas, and global collaboration networks. This study highlights the creative significance of materials like metal–organic frameworks, carbon-based nanocomposites, and MXenes, which have been instrumental in advances, especially in hybrid systems that improve robustness and sensitivity. Offering an in-depth perspective on current research directions and emerging topics, this review explores areas like eco-friendly nanocomposites and additive manufacturing. Highlighting the relevance of biodegradable materials in supporting global sustainability efforts, it provides insights into future opportunities for advancing multifunctional nanocomposites in sensing technologies.